PENINGKATAN KEGIATAN SOSIAL EKONOMI MASYARAKAT TERHADAP PENDAPATAN PENGELOLA EKOWISATA MANGROVE PULAU BUNGKUTOKO KOTA KENDARI - Waode Muamalah Lestari; La Onu La Ola; Sjamsu Alam Lawelle (Jurnal Bisnis Perikanan (Journal of Fishery Business), 2017)
The study aim was to analyze income gained by mangrove ecotourism manager from ecotourism services contribution, park areas, and income of micro business at mangrove ecotourism and to know type of social economie activities held at mangrove ecotourism of Bungkutoko Island. Data collection was taken through direct interview and fill up a questionaire. Sampling technique was choosen purposively with total samples of 11 households and 30 tourists. Data was analysed descriptevely. Based on the analysis that income gained from ecotourism service contribution by ecotourism manager was Rp.23,250,000/month while from contribution of park area of ecotourism was Rp.6,400,000/month. Maximum income gained by micro businessmen was Rp.30,000,000/month. Social activities done at mangrove ecotourism were regular social gathering, meeting health center staffs, student learning activities at an open space, scouts meeting the village officials, and mangrove planting activities. Economic activities done by local community was micro business activity and economic activities such as services